2020
DOI: 10.1007/s00439-020-02194-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of telomere length in men who carry a fragile X premutation or full mutation allele

Abstract: The fragile X premutation is defined by the expansion of the CGG trinucleotide repeat at the 5′ UTR of the FMR1 gene to between 55 and 200 repeats, while repeat tracks longer than 200 are defined as full mutations. Men carrying a premutation are at increased risk for fragile X-associated tremor/ataxia syndrome (FXTAS); those with > 200 repeats have fragile X syndrome, a common genetic form of intellectual disabilities. In our study, we tested the hypothesis that men carrying a fragile X premutation or full mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…[193][194][195][196][197][198][199][200]. Shorter telomeres have been described in PBMCs of PM males compared to controls or FM carriers, regardless of FXTAS or dementia diagnosis [201][202][203]. In PM female carriers, this shortening was also present, although the difference related to control donors was more evident with a FXPOI diagnosis in young individuals [204].…”
Section: Telomere Shortening In Premutation Carriersmentioning
confidence: 99%
“…[193][194][195][196][197][198][199][200]. Shorter telomeres have been described in PBMCs of PM males compared to controls or FM carriers, regardless of FXTAS or dementia diagnosis [201][202][203]. In PM female carriers, this shortening was also present, although the difference related to control donors was more evident with a FXPOI diagnosis in young individuals [204].…”
Section: Telomere Shortening In Premutation Carriersmentioning
confidence: 99%
“…Men carrying a premutation are at increased risk for fragile X-associated tremor/ataxia syndrome (FXTAS). It was recently demonstrated that premutation carriers had shorter telomeres compared with non-carriers, and that telomere shortening may be a consequence of the toxic effect of the premutation transcript with still undefined mechanisms [135].…”
Section: Undefined Mechanismsmentioning
confidence: 99%